ONLINE IMPULSE BUYING; FACTORS EFFECT OF IMPULSIVE SYSTEM STIMULI AND ORGANISM - Siska Maryunitasari; Adi Santoso; Naning Kristiyana (International Journal of Artificial Intelligence Research, 2022)
This study aims to explore the factors that influence impulse buying behavior on social commerce platforms caused by review quality, source credibility, and observational lierning which are mediated by positive effects. The population of this study is consumers on social commerce platforms. A total sample of 318 respondents. This research method is path analysis with analysis tools using the statistical software AMOS 24. This research found that review quality and source credibility had no effect on the positive effect, but observational lierning had a significant effect on the positive effect. The results of this research also found that review quality, source credibility, and positive effect affected impulse buying behavior, but observational lierning had no significant effect on impulse buying behavior. Furthermore, the positive effect can mediate the relationship between observational lierning and impulse buying behavior, but cannot mediate between review quality, and source credibility on impulse buying behavior. Marketers to increase impulsive buying behavior must create a positive effect on consumers and must also pay attention to review quality, source credibility, and observational lierning because these three things can increase impulsive buying behavior. So that should be the full attention of the company. The results of this study have a novelty that can be used to extend theoretical research. Research with this new research model also reveals the understanding that social interaction can motivate impulsive buying behavior. Meanwhile, this research also discusses the effects of mediating variables.